Water Erosion Modelling in the Algerian Steppe Zones: Case of Laghouat Province - Yamani Kheira; Hazzab Abdelkrim; Sekkoum Mohamed; Korichi Khaled (Journal of Landscape Ecology, 2025)
Water erosion is a complex environmental phenomenon that affects many countries around the world. In this paper, remote sensing data, and environmental and climatic indicators are used to map the soil erosion extent in the Laghouat steppe region in central Algeria. This area is characterized by low rainfall of limited duration and high intensity. As a result, the vegetation cover is low and soil abrasion is remarkable. Using the EPM erosion potential model, satellite data provides information on environmental indicators such as slope, soil, vegetation cover, and climatic factors such as annual precipitation and temperature. The results show that the average soil losses modeled by the EMP are calculated at 28 t/ha/year representing a range from 0.52 to 340 t/ha/year. Statistical analysis of these results also determines the highly correlated factors that control water erosion in this area, including slope, rainfall, and soil sensitivity.